1999
DOI: 10.1097/00043426-199905000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Alloimmunization in Preterm Infants After Transfusion of Fresh Unmodified Versus Stored Leukocyte-Reduced Red Blood Cells

Abstract: Preterm infants rarely produce antibodies to blood cell antigens after RBC transfusions, regardless of whether the exposure is to fresh unmodified RBCs from several donors or to stored leukocyte-reduced RBCs from a limited number of donors. Therefore, efforts to limit donor exposures or to remove WBCs from blood components cannot be justified simply for purposes of preventing alloimmunization in neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 24 publications
3
36
0
Order By: Relevance
“…The formation of red cell antibodies may be influenced by the patients' age at which the transfusions are given or when chronic transfusion therapy is started. Four studies on RBC alloimmunization performed in (pre-term) neonates who received multiple transfusions during the first 3-4 months of life did not encounter any RBC antibodies [202][203][204][205] 165,171,196,198,201 . The conflicting results are explained by the number of transfusions, the interval between transfusionsevents, the frequency of antibody testing (single versus serial) and the specificity of the antibodies (e.g.…”
Section: Red Blood Cell Antibodies In Diseasementioning
confidence: 95%
“…The formation of red cell antibodies may be influenced by the patients' age at which the transfusions are given or when chronic transfusion therapy is started. Four studies on RBC alloimmunization performed in (pre-term) neonates who received multiple transfusions during the first 3-4 months of life did not encounter any RBC antibodies [202][203][204][205] 165,171,196,198,201 . The conflicting results are explained by the number of transfusions, the interval between transfusionsevents, the frequency of antibody testing (single versus serial) and the specificity of the antibodies (e.g.…”
Section: Red Blood Cell Antibodies In Diseasementioning
confidence: 95%
“…Human studies have not noted an association between the duration of RBC storage and recipient alloimmune responses [42,43,44], although one recent study has shown a correlation between storage time and in vitro phagocytosis [45]. Potentially important considerations in the interpretation of these studies, however, include the definition of an ‘older' RBC unit as well as whether the recipients received fresh RBCs in combination with older RBCs.…”
Section: Donor- or Product-specific Factorsmentioning
confidence: 99%
“…AIDS patients may not form anti-D after D-mismatched transfusions at all, possibly attributable to their immunosuppressed state with CD4-positive T-cell deficiency [48]. Likewise, also preterm infants known to have an immature immune system are unlikely to form RBCA [56]. It can be suspected that also very old patients have a blunted immune response towards RBC antigens; however, part of such reduced alloimmunization tendency will be counterbalanced by a higher risk for secondary immunization based on anamnestic exposure throughout earlier decades of life.…”
Section: Clinical Factors Influencing Red Blood Cell Alloimmunizationmentioning
confidence: 99%